Por uma ontologia plana: Harman, Simondon, Peirce - Jungk, Isabel Victoria Galleguillos (2017)
By the emergence of the Internet of Things as a physical extension of the network, characterized by the interconnection of intelligent, autonomous and sentient objects, man has lost the position of absolute master in those interrelations to be another actor in the theater of the intricate transformations that take place, evincing the need to rethink the ontological status of both human and technical beings. In the scope of Speculative Realism, the proposal of an Object Oriented Ontology by Graham Harman arose, claiming an ontology which does not depart from pre-established hierarchies between different types of beings. However, despite the undeniable value of the contributions that this movement has made, such as the intense questioning of the subject-object relationship, the importance given to the relation and the disregard of representational issues stricto sensu, such contributions do not seem to suffice for building a philosophy on a truly realistic ground. In this context, it is raised the question about the possibility of the existence of a common denominator between human beings and technical entities, which would be capable of grounding a realistic ontology devoid of pre-established hierarchies. In the present study, it is hypothesized that this gap can be fulfilled by the ontologies elaborated in the works of Gilbert Simondon and Charles Sanders Peirce, authors whose philosophies stand out for metaphysics of an eminently logic and scientific nature, but which do not yet appear in the theoretical framework of contemporary realism in a significant manner, pointing to the relevance of this research. The results of this hypothetical-deductive research are expected to lead to the scientificmetaphysical foundation of a renewed ontological perspective, capable of addressing the consequences of the coexistence between humans and technical beings, as a result of the emerging intelligence technologies, on a realistic and non-hierarchical basis